Persepsi Generasi Z Terhadap Keterlibatan Ayah Dalam Pengasuhan Anak: Kajian Literatur Pada Penelitian Digital Parenting - Shafa Azira Rachma; Maulidya Maulidya; Shakila Malva Fauziyah; Salma Fatma (Jurnal Keluarga Sehat Sejahtera, 2026)
This study aims to examine father involvement in the context of digital parenting and its implications for the character development of Generation Z. The study employed a literature review method by analyzing relevant scientific publications on father involvement, digital resilience, self-control, and parenting in the digital era. The findings indicate that father involvement positively contributes to children's self-control, emotional regulation, and psychological resilience. Fathers also play a significant role in developing digital resilience by acting as guides, supervisors, supporters, and mediators in children's technology use. Active father participation in digital parenting helps children cope with digital risks more wisely and responsibly. These findings highlight that father involvement is a crucial component of modern parenting that adapts to technological advancements. However, its implementation still faces challenges, including limited time availability and gaps in digital literacy. This study contributes to the growing body of knowledge on father involvement in digital parenting and provides a basis for developing parental capacity-building programs in the digital era.